2003
DOI: 10.1099/jmm.0.05173-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of acquired immunity to Salmonella

Abstract: Salmonella enterica serovar Typhi (S. typhi) causes human typhoid fever, a serious and widespread disease in developing countries. Other Salmonella serovars are associated with food-borne infections. The recent emergence of multi-drug-resistant Salmonella strains highlights the need for better preventive measures, including vaccination. The available vaccines against Salmonella infection do not confer optimal protection. The design of new Salmonella vaccines must be based on the identification of suitable viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 103 publications
(85 reference statements)
3
80
0
1
Order By: Relevance
“…Following invasion, it is hypothesized that Salmonella spp. are taken up by the macrophages and dendritic cells and subsequently transported via the lymphatic system to the spleen and the liver (Mastroeni & Menager, 2003;Chappell et al, 2009). We observed that the overcrowding stress decreased the intensity of macrophage phagocytosis in the chickens of Group POv.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Following invasion, it is hypothesized that Salmonella spp. are taken up by the macrophages and dendritic cells and subsequently transported via the lymphatic system to the spleen and the liver (Mastroeni & Menager, 2003;Chappell et al, 2009). We observed that the overcrowding stress decreased the intensity of macrophage phagocytosis in the chickens of Group POv.…”
Section: Discussionmentioning
confidence: 52%
“…Indeed, Salmonella migration could happen both to the spleen and liver following invasion since Salmonella is assumed to be taken up by macrophages and transported via the lymphatic system to the spleen and liver (Mastroeni & Menager, 2003;Chappell et al, 2009). However, there is no firm experimental evidence to define the main target organ of Salmonella invasion (Mastroeni & Menager, 2003;Chappell et al, 2009). It seems feasible to suggest that bacterial invasion is not controlled by the innate immune system and that Salmonella is able to reach and replicate within several organs (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…74 and our unpublished observations) and are cleared by immunocompetent hosts, whereas virulent Salmonella rapidly overwhelm host defenses. The growth advantage of virulent bacteria is eliminated by prior immunization, as immune host T and B cell functions provide protection (75,76). Interestingly, memory T cells express CCR6, the only known receptor for CCL20, a chemokine secreted by intestinal epithelial cells after stimulation by flagellin (77).…”
Section: Discussionmentioning
confidence: 99%
“…Both these vaccines are well tolerated but are only moderately protective (Ivanoff et al 1994;Keitel et al 1994;Merican 1997;Levine et al 1999;Allam et al 2011). The emergence of multidrug-resistant (MDR) strains of S. Typhi and limited scope of available vaccine (Mastroeni & Menager 2003) against Salmonella infection has added a sense of urgency to evaluate the efficacy of different immunogens to develop more effective typhoid vaccines.…”
Section: Introductionmentioning
confidence: 99%